Neuroendocrinal, Neurodevelopmental, and Embryotoxic Effects of Recombinant Tissue Plasminogen Activator Treatment for Pregnant Women with Acute Ischemic Stroke - Steinberg, Anna; Moreira, Tiago P. (Frontiers in Neuroscience, 2016)
Thrombolysis with recombinant tissue plasminogen activator (rTPA) was the first evidence-based treatment approved for acute stroke. Ischemic stroke is relatively uncommon in fertile women but treatment is often delayed or not given. In randomized trials, pregnancy has been an exclusion criterion for thrombolysis. Physiologic TPA has been shown to have neuroendocrine effects namely in vasopressin secretion. Important TPA effects in brain function and development include neurite outgrowth, migration of cerebellar granular neurons and promotion of long-term potentiation, among others. Until now, no neuroendocrine side-effects have been reported in pregnant women treated with rTPA. The effects of rTPA exposure in the fetus following intravenous thrombolysis in pregnant women are still poorly understood. This depends on low case frequency, short-duration of exposure and the fact that rTPA molecule is too large to pass the placenta. rTPA has a short half-life of 4-5 min, with only 10% of its concentration remaining in circulation after 20 min, which may explain its safety at therapeutically doses. Ischemic stroke during pregnancy occurs most often in the third trimester. Complication rates of rTPA in pregnant women treated for thromboembolic conditions and ischemic stroke were found to be similar when compared to non-pregnant women (7 to 9% mortality). In embryos of animal models so far, no indications of a teratogenic or mutagenic potential were found. Pregnancy is still considered a relative contraindication when treating acute ischemic stroke with rTPA, however, treatment risk must be balanced against the potential of maternal disability and/or death.